Plan de marketing de los recursos turísticos de la parroquia Santiago, cantón San Miguel, provincia Bolívar, año 2011 - Quiroz Becerra, Jafferson Estuardo (2012)
This paper begins to describe the real tourist activity in Santiago Parish, which in the last decade had not gained importance for the development of the town, because economic development is mostly given by the practice of agricultural activities, few people are engaged in trade and other kind of business, but there is no real commitment to tourism. Then we present to you the general objective of this research and the steps followed to achieve them: The first one was make a diagnosis of the current situation of Santiago Parish, through this we could know different areas such as: geographical, historical, social, cultural and economic aspects of the town; after that we made a diagnosis of the current tourism product, here we have a description of each actual and potential tourist resources in addition to explaining the real situation of the destination. Below we did a Market Research, analyzing the competitive position of Santiago parish, and finally the Tourism Plan of Marketing was designed, this research provides strategies, that enabling direct targeting different markets, as well as also considers and seeks the positioning of Santiago as a tourist destination, it extends the offer existing in the country and generates greater economic contribution and development to the country.